PENDIDIKAN KARAKTER DI BAPAS SURAKARTA DAN IMPLIKASINYA TERHADAP PENANGGULANGAN KRIMINALITAS PENCURIAN (STUDI KASUS TERHADAP ANAK PELAKU TINDAK KRIMINALITAS PENCURIAN DI KOTA SURAKARTA) - Sugiyatmi, Sri (Educitizen, 2013)
The objectives of research are to find out: 1) the function of BAPAS in conducting character education to the children committing stealing crime in Surakarta, and 2) the implication of character education in BAPAS to the stealing crime handling in Surakarta city.This study was a descriptive qualitative method. The research strategy used was a single embedded strategy. The data source was obtained from informant, event/activity and document. The sampling technique used was purposive sampling. Techniques of collecting data used to obtain and to organize the data of research were interview, observation as well as document analysis. To validate the data, the data triangulation was used. Meanwhile the technique of analyzing data used was an interactive model of analysis with the following steps: 1) Data collection, 2) Data reduction, 3) Data display, 4) Conclusion drawing/verification. The procedure of research included: 1) preparation, 2) data collection, 3) Data analysis, and 4) Research report writing stages.